Problems Of Increasing The Efficiency Of Bank Credits To Ensure Macroeconomic Sustainability - Zafarjon Yashinovich Rakhmanov; Fakhritdin Mannonovich Daminov; Umidjon Bakhtiyorovich Abulkhaev (The American Journal of Management and Economics Innovations, 2021)
One of the main factors in ensuring the macroeconomic stability of the country in the post-pandemic period is to increase the efficiency of loans provided by commercial banks. This article examines the issues of improving the efficiency of loans provided by commercial banks in ensuring macroeconomic stability of the country in the event of a pandemic. In addition, through the analysis of the current situation in the banking system, systemic risks were identified and proposals and recommendations were developed to improve the efficiency of credit operations.